PENGARUH TEKNIK BERBALAS PANTUN UNTUK MENINGKATKAN KEPERCAYAAN DIRI SISWA SMP MELALUI BIMBINGAN KELOMPOK DI SMP MUHAMMADIYAH 1 PEKANBARU - Nurdian Ningsih; Zulfan Saam; Donal Donal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the description of students' self-confidence before and after given the pantun-reply technique, differences in students' self-confidence before and after given the pantun-reply technique and to increase students' self-confidence through group guidance. This research was conducted at Pekanbaru Muhammadiyah 1 Middle School towards 8 subjects with purposive sampling technique. The design of this study was pre-experiment with the one group pretest-posttest model. The data collection instrument used was an instrument consisting of indicators of student self-confidence before and after being given the pantun reply technique through group guidance with a significant value of 0.012 <0.05. The confidence of the 8 previous students was in the low category, increasing after being given the pantun reply technique through group guidance, most of which were in the high category. In addition, based on the rank spearman test, it was observed that there was a significant effect of the pantun reply technique on students' self-confidence by 78% while 22% was influenced by other factors that came from within the students and the environment.Key Words: Pantun Rewarding Technique, Self Confidence, Group Guidance